Metapragmatic reflections of adolescents on gender in ironic interactions - Hess Zimmermann, Karina; Avecilla-Ramírez, Gloria Nélida; Castillo Romo, Abryl Angélica (Frontiers in Language Sciences, 2024)
While verbal irony is a pragmatic skill that plays a very important role in social interactions, its development has not been sufficiently studied, especially in the context of the Spanish language. This research aims to generate a deeper understanding of the development of irony, specifically among Mexican adolescents. One of the pragmatic aspects identified as an important factor to consider in the comprehension and production of verbal irony is the gender of the participants involved in the communicative interaction. Prior research with adults indicates that ironic statements produced by men are generally associated with positive discursive functions, whereas those made by women are often perceived negatively. This study aims to analyze the metapragmatic reflections of 37 Mexican adolescents aged 12 and 15 years old (20 and 17 participants, respectively, half women) on how the gender of the interlocutors influences the use of irony in various communicative situations. Participants were presented with eight written scenarios that concluded with a written ironic statement (in order to minimize the effects of prosody). The scenarios were counterbalanced to account for the type of ironic remark (critical or praise irony), the gender of the ironist, and the gender of the audience. Through a semi-structured oral interview, the adolescents' reflections and the rationale behind their responses were examined. The results revealed significant differences in the interpretation of irony based on age, type of statement (criticism or praise), and the gender of the interlocutors, though not with respect to the gender of the audience. Additionally, a discrepancy was observed between the metapragmatic reflections expressed by adolescents regarding ironic statements and their actual interpretation of irony. These findings suggest that during adolescence, individuals develop an increasing capacity to consider factors related to gender roles that influence the pragmatic interpretation of ironic statements.